El estado de aplicación del concepto de redes sociales en línea como una herramienta de mercadeo en Costa Rica a abril 2009 - Araya-Sancho, Laura Elena; Murillo-Delgado, Walter; Novoa-Jiménez, Allan; Sancho-Corrales, Nancy (Instituto Tecnológico de Costa Rica., 2009)
Social networking is a global phenomenon that is increasingly seeping into our culture and constitutes a new means of interaction between individuals who identify and engage with each other, creating communities of users who become increasingly important potential consumer markets for many products and services. As in the rest of the world, in Costa Rica more and more companies create social networks and engage in social networks as part of its marketing strategy, getting more and more users, who will identify with their network or organization as part of another network. In the particular situation of our country, it can be identified the sectors that have managed to create more followers are affiliated companies devoted to leisure or entertainment. However, more recently, as has been the national policy also makes its own in this area, particularly emulating American experience and demonstrated success in using social networks in recent U.S. electoral contests. At the same time many companies and individuals offer diverse range of products and services, and move into marketing networks in order to expand their markets by investing a smaller amount of capital. This study investigates the application and use of social networks in Costa Rica as a marketing tool, giving it the importance it has acquired the item in the environment and the promise of becoming a fundamental tool for trading goods and services. Therefore describes the main marketing applications developed in our country in social networking, as well as a preamble to the way that appears to take a short-term future. It also identifies key strengths, weaknesses, and important facts to consider in ensuring the success of a social network and the key to increasing the effectiveness of the marketing networks. The research provides a better understanding about the social networks with greater participation in Costa Rica and the world, the main users and consumers, as well as their status of implementation as a marketing tool in Costa Rica. The more you know the market you want to cover, the greater the chance of success.
Proyecto de Graduación (Licenciatura en Administración de Empresas. Enfasis en Mercadeo) Instituto Tecnológico de Costa Rica, 2009.
Keywords: Mercadotecnia; Mercadeo electrónico; Comercio electrónico; Redes sociales; Costa Rica